LCC implementation and its benefits towards the community in Shah Alam / Farah Nadia Azhar, Nor Azira Ayob and Zarina Mohd Zain - Azhar, Farah Nadia; Ayob, Nor Azira; Mohd Zain, Zarina (2022)
Low Carbon City (LCC) is a city which comprise of societies that consume sustainable green technology, green practices, and emit relatively low carbon or greenhouse gases (GHG). The concept of LCC is closely related to the sustainable development of a city. With the adoption of sustainability principles, carbon emissions can be reduced significantly through the means and ways in which cities are designed and developed, and the ways resources are consumed. The main objective of this study is to determine the factors in implementing the LCC program and the benefits that the community gain from the program. The factors and the benefits were identified from several past studies. Therefore, a total of 3 respondents were chosen to provide information in order to gather data for this study. The respondents are the officials who in charged directly with the LCC programs. This study found that the factors that contribute to the implementation of LCC is measured through three main areas: 1) environment; 2) transportation; and 3) infrastructure. Whereas the benefits were identified in terms of economy, social and health. This study provides an insight on the importance of having Low Carbon City program in Shah Alam while also indirectly raising the community’s awareness and ensuring their acceptance towards the LCC program. Furthermore, the findings from this research can also be adopted by other local governments for the implementation of the program.